Integrating GIS With Image Database And Its Role In The Development Of Marine Minerals - Jun Lu (International Marine Minerals Society, 2000)
Compared with land mineral resources investigation, as well known, it is more important for marine geologists to get image data (e.g. photographs, video tapes and various charts) because they are often hard to reach deep seabed directly. In the past years a plenty of image data which are in various forms have been accumulated. In contrast with both digital and character data managing the image data by using database is just unfolding and it will be a trend for marine mineral resources investigation. GIS (Geography Information System) offers another useful means of processing image data, especially geological data. GIS is characterized by processing vector data (e.g. point, line and polygon), but newer versions of GIS software package are also able to process raster data (e.g. photographs etc.). The present author made a presentation on marine mineral image database during 25th UMI, but that system runs under DOS environment and dealt with only mineralogy. Recently a new system which integrates Oracle image database with GIS (ArcView version 3.1) has been developed. This system runs under Windows NT environment. In the network environment Server/Client mode is adopted, and over 200 basic subdatabases (tables)are located on Server; operating interfaces are located on several clients so that several persons can operate the system simultaneously. The whole system involves five types of marine mineral resources: manganese nodules, cobalt-rich crusts, polymetallic sulfides, phosphorites and gas hydrates. The data of every type of marine mineral resources described above are distributed among five units and several blocks. The units and blocks are described below: